2017
DOI: 10.1523/jneurosci.0005-16.2016
|View full text |Cite|
|
Sign up to set email alerts
|

A Critical Role for Astrocytes in Hypercapnic Vasodilation in Brain

Abstract: Cerebral blood flow (CBF) is controlled by arterial blood pressure, arterial CO2, arterial O2, and brain activity and is largely constant in the awake state. Although small changes in arterial CO2 are particularly potent to change CBF (1 mmHg variation in arterial CO2 changes CBF by 3%–4%), the coupling mechanism is incompletely understood. We tested the hypothesis that astrocytic prostaglandin E2 (PgE2) plays a key role for cerebrovascular CO2 reactivity, and that preserved synthesis of glutathione is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 57 publications
1
74
0
Order By: Relevance
“…Finally, a recent study has suggested that astrocytes may also mediate cerebrovascular responses to CO 2 . Howarth and colleagues (2017) reported that in anesthetized mice, increases in the level of inspired CO 2 trigger [Ca 2+ ] i responses in cortical astrocytes, which in turn may evoke cerebral vessel dilations via stimulation of COX‐1 activity followed by PgE 2 release and its action on cerebrovascular smooth muscle cells (Howarth et al, ).…”
Section: Astrocytes As Cns Metabolic Sensorsmentioning
confidence: 99%
“…Finally, a recent study has suggested that astrocytes may also mediate cerebrovascular responses to CO 2 . Howarth and colleagues (2017) reported that in anesthetized mice, increases in the level of inspired CO 2 trigger [Ca 2+ ] i responses in cortical astrocytes, which in turn may evoke cerebral vessel dilations via stimulation of COX‐1 activity followed by PgE 2 release and its action on cerebrovascular smooth muscle cells (Howarth et al, ).…”
Section: Astrocytes As Cns Metabolic Sensorsmentioning
confidence: 99%
“…The ‘feed-forward’ hypothesis of neurovascular coupling (Attwell et al 2010) suggests that neurotransmitters released during neuronal activity signal to astrocytes and pericytes to induce dilation of the cerebral vasculature (Mishra et al 2016). However, astrocytes are also sensitive to changes in partial pressure of oxygen (PO 2 ) (Angelova et al 2015) as well as CO 2 and protons (H + ) (Gourine et al 2010; Howarth et al 2017; Karagiannis et al 2016). Changes in brain tissue PO 2 , PCO 2 and pH correlate with changes in neuronal activity and could contribute to neurovascular coupling via a metabolic feed-back mechanism, as was originally proposed by Roy and Sherrington (Roy and Sherrington 1890).…”
Section: Introductionmentioning
confidence: 99%
“…ATP is released from the ventral medullary surface in response to CO 2 and [H + ] 3 and contributes to the activation of the respiratory network 3 , 4 . Astrocytes can sense CO 2 and H + in neocortex 5 , 6 and act as chemosensory interoceptors in the rat rostral medullary brainstem 4 , 7 where they release ATP 4 , 7 to activate H + -sensitive retrotrapezoid neurons 4 , 8 10 in response to acidosis or hypercapnia (increased levels of CO 2 ) 4 . However, experimental results supporting the theory that hypercapnia in the caudal medullary brainstem is also mediated by ATP have been elusive 11 .…”
Section: Introductionmentioning
confidence: 99%